2023
DOI: 10.1111/gbi.12575
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and authigenic siderite mediation in sediments surrounding the Kedr‐1 mud volcano, Lake Baikal

Anna V. Lomakina,
Sergei V. Bukin,
Tatyana V. Pogodaeva
et al.

Abstract: The gas hydrate‐bearing structure—mud volcano Kedr‐1 (Lake Baikal, southern basin)—is located near the coal‐bearing sediments of the Tankhoy formation of Oligocene–Miocene age and can be an ideal source of gas‐saturated fluid. A significant amount of siderite minerals (FeCO3) were collected from sediments at depths ranging from 0.5 to 327 cm below the lake floor (cmblf). An important feature of these carbonate minerals is the extremely strong enrichment in the heavy 13C isotope, reaching values of +33.3‰ VPDB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 140 publications
1
0
0
Order By: Relevance
“…For functional groups, the abundances of some microbial communities were correlated to their ecological function in the ecosystem. Our findings, as well as previous studies, have all shown that fermentation was the most important metabolic pattern in sediment samples ( Huang et al, 2020 ; Liu et al, 2023 ; Lomakina et al, 2023 ). The reason for this could be illustrated by the fact that the saline lake sediment is an anaerobic environment that lacks oxygen while being rich in organic matter ( Wasmund et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…For functional groups, the abundances of some microbial communities were correlated to their ecological function in the ecosystem. Our findings, as well as previous studies, have all shown that fermentation was the most important metabolic pattern in sediment samples ( Huang et al, 2020 ; Liu et al, 2023 ; Lomakina et al, 2023 ). The reason for this could be illustrated by the fact that the saline lake sediment is an anaerobic environment that lacks oxygen while being rich in organic matter ( Wasmund et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%